Evaluation of complete diesel replacement using propanol and biodiesel blends with carbon nanotube additives - Celebi, Yahya (Nature Portfolio, 2025)
As environmental concerns intensify globally and regulations on fossil fuel consumption become increasingly stringent, the development of clean, sustainable energy sources for diesel engines has become an urgent priority. With this aim, this research explored complete diesel replacement with biodiesel-propanol and three carbon nanotube types. These carbon nanotubes (SWCNT, DWCNT, and MWCNT) were added to biodiesel-propanol blends (90% biodiesel, 10% propanol) at 100 ppm concentration. Engine tests were performed at 1500 rpm and various operation loads. Combustion analysis revealed that SWCNT and MWCNT blends increased cylinder pressure by 0.2% and 0.7%, respectively, while DWCNT reduced it by 11.9% compared to diesel. Heat release rates improved by 13.1%, 11.2%, and 13.0% for SWCNT, DWCNT, and MWCNT blends, respectively. Performance metrics showed increased brake specific fuel consumption for all carbon nanotube blends compared to conventional diesel, with average increases of 9.2% for SWCNT, 12.7% for DWCNT, and 13.2% for MWCNT. Despite higher fuel consumption, brake thermal efficiency improved with B90 + SWCNT, achieving the highest gain at 6.3%, followed by DWCNT (3.1%) and MWCNT (1.5%). Emissions testing demonstrated significant benefits, with nitrogen oxides emissions decreasing by 8.4% (MWCNT), 7.6% (DWCNT), and 7.3% (SWCNT). Hydrocarbon emissions improved by up to 40.2% with carbon nanotube inclusion, particularly at higher loads. MWCNT was the most effective for reducing carbon monoxide and carbon dioxide emissions. These findings suggest MWCNT-enhanced blends could replace conventional diesel with lower emissions despite slightly higher fuel consumption.
Keywords: Biodiesel; SWCNT; DWCNT; MWCNT; Propanol; Diesel engine